ACCase and rbcL gene expression as a function of nutrient and metal stress for enhancing lipid productivity in Chlorella sorokiniana. (15th September 2017) - Singh, Poonam; Kumari, Sheena; Guldhe, Abhishek; Singh, Gulshan; Bux, Faizal
Highlights: Combined metals stress alleviate low biomass constraint under limited N and P. Developed strategy improved lipid productivity by 2.3 times in C. sorokiniana . Upregulation of rbcL and accD genes observed under high Fe in late log phase. Upregulation of accD observed under high magnesium in mid and late log phases. Lipid productivity was influenced most significantly by Fe followed by Mg. Abstract: Development of novel and scalable strategies for improving lipid and biomass yield is a prerequisite for sustainable biodiesel production from microalgae. Currently, nutrient stress is the widely employed lipid enhancement strategy in microalgae, yet, it is associated with compromised biomass productivity. In this study, an alternative approach for lipid enhancement in Chlorella sorokiniana is proposed to alleviate the constraint of low biomass production under nutrient stress. This is achieved through combining nutrient stress along with selected metals and EDTA stress. A substantial increase in lipid yield (77.03 mg L −1  d −1 ) was achieved when the nutrient (nitrogen and phosphorus) stress BG11 media was supplemented with a combination of iron (15 mg L −1 ), magnesium (125 mg L −1 ), calcium (18 mg L −1 ) and EDTA (3 mg L −1 ). This was further validated by quantifying the expression levels of two key genes involved in photosynthesis ( rbcL ) and lipid biosynthesis ( accD ) pathways. Under this developed strategy a 5.15-fold increase in rbcL and 9.79-fold increases in accD gene expression were noted in comparison to the culture grown in BG11 medium. A significant correlation could also be drawn between the expression of rbcL and accD genes to biomass yields, photosynthetic performance and lipid productivity. The proposed strategy could be easily applied at various commercial scale microalgal cultivation systems for enhancing lipid content without compromising the biomass yield.